Maternal and fetal outcomes of pregnancies in kidney donors: A 30-year comparative analysis of matched non-donors in a single center - Kyung Don Yoo; Hajeong Lee; Yaerim Kim; Sehoon Park; Joong Shin Park; Joon Seok Hong; Chang Wook Jeong; Hyeon Hoe Kim; Jung Pyo Lee; Dong Ki Kim; Kook-Hwan Oh; Kwon Wook Joo; et al. (The Korean Society of Nephrology, 2018)
Background : Woman kidney donors face obstetric complication risks after kidney donation, such as gestational hypertension and preeclampsia. Studies on childbirth-related complications among Asian women donors are scarce. Methods : This retrospective cohort study included woman donors aged 45 years or younger at the time of kidney donation in a single tertiary hospital between 1985 and 2014. Pregnancy associated complications were investigated using medical records and telephone questionnaires for 426 pregnancies among 225 donors. Matched non-donor controls were selected by propensity score and the maternal and fetal outcomes were compared with those of donors. Primary outcomes were differences in maternal complications, and secondary outcomes were fetal outcomes in pregnancies of the donor and control groups. Results : A total of 56 cases had post-donation pregnancies. The post-donation pregnancies group was younger at the time of donation and older at the time of delivery than the pre-donation pregnancies group, and there were no differences in primary outcomes between the groups except the proportion receiving cesarean section. Comparison of the complication risk between post-donation pregnancies and non-donor matched controls showed no significant differences in gestational hypertension, preeclampsia, or composite outcomes after propensity score matching including age at delivery, era at pregnancy, systolic blood pressure, body weight, and estimated glomerular filtration ratio (odds ratio, 0.63; 95% confidence interval, 0.19-2.14; P = 0.724). Conclusion : This study revealed that maternal and fetal outcomes between woman kidney donors and non-donor matched controls were comparable. Studies with general population pregnancy controls are warranted to compare pregnancy outcomes for donors.